TINGKAT MASTERY GOAL ORIENTATION SISWA SEKOLAH DASAR DI KABUPATEN BEKASI - Ida Saidah; Budi Sarasati (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to analyze the relationship between mastery goal orientation and growth mindset among elementary school students. Mastery goal orientation is defined as a learning orientation focused on mastering subject matter, developing competence, and demonstrating academic progress through sustained effort. This research employed a quantitative method using a survey design and descriptive analysis. Respondents were drawn from 313 public and private elementary schools in Bekasi Regency. The research instrument was a mastery goal orientation scale adapted from Slavin (2003), modified into nine characteristics relevant to the developmental stage of elementary school students. Data were analyzed using t-tests and analysis of variance (ANOVA) with SPSS 23. The results indicated no significant differences in mastery goal orientation across gender, age, grade level, or school type. However, overall findings highlight that mastery goal orientation positively contributes to the development of a growth mindset, particularly in terms of strategic approaches to challenges, enthusiasm within the learning environment, and the principle of continuous growth. These results underscore the crucial role of teachers in fostering mastery-oriented learning, perseverance, and positive interpretations of failure.